Imagen corporal y calidad de vida en pacientes con insuficiencia renal crónica en tratamiento de hemodiálisis del Hospital General Isidro Ayora de Loja, periodo 2018- 2019 - Reza Narváez, Lizbeth Catherine (2019)
The research entitled Body Image and Quality of Life in Patients with Chronic Renal Insufficiency (CRI) in treatment at Isidro Ayora General Hospital of Loja, period 2018-2019. It allowed to determine the perception of body image and quality of life in patients with CRI. In the sample of 50 patients, 25 females and 25 males. It was used the quantitative approach, with transversal and descriptive design; for data collection it was carried out through the Body Image Scale (BIS - women), Multidimensional Body Self Relation Questionnaire (MBSRQ - men), SF-36 Health Questionnaire (quality of life) and the SPSS V25 statistical program, with the statistical correlation formula Rho of Spearman and correlation of Pearson. The results obtained were the 40% of regular affectation in women and 96% regular alteration in men in the body image variable, when assessing quality of life, 34% male and 36% female presented good quality of life, deducing that there is no relationship between the two variables. As a general conclusion it is believed that the no relation between body image and quality of life is due to the fact that the time that patients with CRI disease are taking is early and it is the reason why their global vision of damage is not affected at the moment. Keywords: Body image, Quality of life, Chronic Renal Insufficiency